Nira Kelapa Dipasteurisasi Sebagai Minuman Penyegar Dengan Variasi Waktu Dan Suhu: Studi Sifat Fisik, Kimia, Mikrobiologi, Dan Sensoris - Bara, Sari Natalia Batu; Wijaya, I Made Mahaputra; Arnata, I Wayan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Coconut sap is a sweet liquid obtained from tapping coconut flowers and has the potential to be developed as a refreshing beverage. However, its shelf life is limited due to spoiling caused by microbial contamination, which lead to fermentation. This study was aimed to determine the optimal pasteurization temperature and duration in order to maintain the physical, chemical, microbiological, and sensory quality of coconut sap. In this study, pasteurization temperatures of 60, 65, and 70 °C for 20, 25, and 30 minutes was applied.. The observed parameters included total microbial count (TPC), pH, total soluble solids (TSS), protein content, ethanol content, color, and sensory evaluation. The results indicated that pasteurization at 70°C for 30 minutes was found to be the best treatment, maintaining microbial counts below the SNI standard up to the 11th day, with protein content of 0.04%, and undetectable ethanol levels. Sensory evaluation results showed high acceptance in terms of color, aroma, and taste.